A block-shaped porous intelligent controlled-release fresh-keeping material and preparation method thereof

By grafting cinnamaldehyde on chitosan and achieving pH response with a porous Schiff base, the stability and release efficiency of cinnamaldehyde in existing fresh-preserving materials is solved, and efficient fresh-preservation of fruits and vegetables is achieved.

CN116082716BActive Publication Date: 2025-03-21XIAN CHI SHI PIN KE JI (JIA XING) YOU XIAN ZE REN GONG SI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211667152.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-03-21
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

Existing fresh-preserving materials have shortcomings in extending the shelf life of fruits and vegetables, especially the poor water solubility and easy degradation of cinnamon aldehyde, which leads to a decrease in its antibacterial activity and making it difficult to achieve accurate release effect.

Method used

Porous bulk chitosan was prepared by ice template method, and cinnamaldehyde was grafted onto chitosan to form imine bonds. The highly humid acidic environment formed during fruit and vegetable storage was used as a response group to achieve the accurate and continuous release of porous Schiff base in pH response.

Benefits of technology

It has achieved the improvement of stability and durability of cinnamaldehyde, and can be accurately released according to the acidic conditions of the storage environment, extending the shelf life of fruits and vegetables. The material is in a blocky and non-contact form, making it more portable, safe and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116082716B_ABST
    Figure CN116082716B_ABST
Patent Text Reader

Abstract

The invention discloses a block-shaped porous intelligent controlled-release fresh-keeping material, which is a grafted cinnamaldehyde prepared from chitosan and cinnamaldehyde and has a porous structure. It can have a sustained-release fresh-keeping effect, and forms a block structure, which is portable, safe and reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of food technology, and in particular to a block-shaped porous intelligent controlled-release fresh-keeping material and a preparation method thereof. Background Art

[0002] Fruits, vegetables and other perishable foods are very easy to rot and deteriorate during storage and transportation due to complex processes such as dehydration, respiratory metabolism, microbial growth and aging. The shelf life is short, resulting in serious food waste. At present, the technologies for extending the shelf life are mainly the following: adding preservatives, radiation and heat treatment, and controlled atmosphere storage. However, excessive use of preservatives may lead to bioaccumulation of toxic substances. Although heat treatment and radiation can reduce the proliferation of microorganisms, they cannot change the maturity of food. Controlled atmosphere storage requires large facilities and a constant supply of gas, which is basically impractical in some areas. In addition, plants have two types of respiratory metabolism: non-climacteric and climacteric metabolism. Fruits and vegetables with different respiratory metabolisms also require different gas compositions in controlled atmosphere storage. Therefore, finding natural and safe alternatives to chemical preservatives has become an inevitable requirement for the storage and preservation of fruits and vegetables. Natural essential oils have the potential to provide quality and safety benefits due to their broad-spectrum antibacterial properties and have little impact on human health, so they are the most promising alternatives.

[0003] Cinnamaldehyde is often used to preserve fruits and vegetables due to its high antibacterial activity, high antioxidant capacity and high safety. However, cinnamaldehyde has poor water solubility and is easily degraded by attacks of light, heat, oxygen and free radicals. The degradation products are benzaldehyde and glyoxal, which reduce the antibacterial activity. Its unique smell also affects the senses. Therefore, it is a new idea to increase the stability and durability of cinnamaldehyde by constructing a delivery carrier. However, in current studies, cinnamaldehyde packaging films, porous microspheres, nanoparticles, etc. cannot match food packaging because their migration rates are controlled by diffusion, and cannot achieve the effect of precise release.

[0004] Therefore, the ice template method was used to control the pore structure by controlling the growth of ice to prepare porous block chitosan, and then cinnamaldehyde was grafted to form an imine bond. The high humidity and acidic environment formed during the storage of fruits and vegetables was used as a probe and the imine bond as a response group to prepare a pH-responsive porous Schiff base to achieve the purpose of precise and sustained release. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the existing fresh-keeping materials, the present invention is proposed.

[0007] Therefore, one of the purposes of the present invention is to overcome the shortcomings of existing fresh-keeping materials and provide a block-shaped porous intelligent controlled-release fresh-keeping material.

[0008] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solution: a block-shaped porous intelligent sustained-release fresh-keeping material, comprising: the fresh-keeping material is a grafted cinnamaldehyde with a porous structure, and the grafted cinnamaldehyde comprises chitosan and cinnamaldehyde. Another object of the present invention is to provide a method for preparing the fresh-keeping material.

[0009] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solution: a method for preparing a block-shaped porous intelligent controlled-release fresh-keeping material, which comprises the following steps:

[0010] Preparation of block porous chitosan: Dissolve chitosan powder in acetic acid solution to form a light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a metal plate, and immerse both ends of the metal plate in a freezing medium. After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. Neutralize the freeze-dried sample in a sodium hydroxide ethanol solution to remove excess acetic acid, then rinse with deionized water to remove excess acid and alkali, wash with alcohol, and dry at room temperature to constant weight to obtain block porous chitosan.

[0011] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, dissolve cinnamaldehyde in ethanol aqueous solution, then pour it into the flat-bottomed flask, and place the flask in a constant temperature heated magnetic stirrer for reaction. After the reaction is completed, change ethanol every 12 hours, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material.

[0012] As a preferred solution of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, wherein: in the preparation of the block porous chitosan, the volume ratio of acetic acid to deionized water is 0.5-2:98-99.5.

[0013] As a preferred solution of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, wherein: in the preparation of the block porous chitosan, the mass volume ratio of chitosan to acetic acid solution is 1-3:97-99.

[0014] As a preferred solution of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, in the preparation of the block porous chitosan, one end or both ends of the metal plate can be placed in a freezing medium by freezing.

[0015] As a preferred solution of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, wherein: in the preparation of the block porous chitosan, the mass volume ratio of sodium hydroxide to ethanol aqueous solution is 0.2-20:80-99.8.

[0016] As a preferred solution of the method for preparing the block-shaped porous intelligent controlled-release fresh-keeping material of the present invention, wherein: in the preparation of the block-shaped porous chitosan, the neutralization time is 5 minutes to 30 minutes.

[0017] As a preferred embodiment of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, in the preparation of the block porous chitosan-cinnamaldehyde Schiff base fresh-keeping material, the molar ratio of the amino group of the porous chitosan to the aldehyde group of the cinnamaldehyde is 1:1-8.

[0018] As a preferred solution of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, wherein: in the preparation of the block porous chitosan-cinnamaldehyde Schiff base fresh-keeping material, the reaction temperature of the porous chitosan and cinnamaldehyde is 20°C to 80°C.

[0019] As a preferred solution of the method for preparing the block porous intelligent controlled-release fresh-keeping material of the present invention, wherein: in the preparation of the block porous chitosan-cinnamaldehyde Schiff base fresh-keeping material, the reaction time of the porous chitosan and cinnamaldehyde is 2h to 24h.

[0020] As a preferred solution of the method for preparing the block-shaped porous intelligent controlled-release fresh-keeping material of the present invention, the fresh-keeping material can be used for the fresh-keeping of bananas.

[0021] The present invention provides a block-shaped porous sustained-release fresh-keeping material with pH response effect, which has the characteristics of acid release and stable medium alkalinity, and also has the following advantages: according to the high humidity and acidity of the headspace environment formed during the storage of fruits and vegetables, the release of cinnamaldehyde can be accurately controlled to preserve the fruits and vegetables. Moreover, the fresh-keeping material is in a block-shaped, non-contact form, which is more portable, safe and reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0023] Figure 1 The scanning electron microscope images of the chitosan porous material after freeze-drying and neutralization in Example 1; the left image is after freeze-drying, and the right image is after neutralization;

[0024] Figure 2 The Fourier transform infrared spectra of the block porous chitosan, the grafted Schiff base material and the cinnamaldehyde in Example 1;

[0025] Figure 3 The release behavior of the grafted Schiff base material in Example 1 in different pH buffers;

[0026] Figure 4 The release behavior of the grafted Schiff base material in Example 1 under different CO2 concentrations;

[0027] Figure 5 The effects of cinnamaldehyde and block Schiff base preservative materials on banana hardness as well as those without treatment;

[0028] Figure 6 The effects of cinnamaldehyde, block Schiff base preservative materials and no treatment on the total number of banana colonies;

[0029] Figure 7 The effects of powdered Schiff base preservative materials, block Schiff base preservative materials treated with or without treatment on the hardness of bananas;

[0030] Figure 8 The effects of powdered Schiff base preservative materials, block Schiff base preservative materials and no treatment on the total bacterial count of bananas;

[0031] Fig. 9 The effects of cinnamaldehyde and block Schiff base preservative materials on grape firmness as well as those without treatment;

[0032] Fig.10 This study examines the effects of cinnamaldehyde and block Schiff base preservative materials on the total bacterial count of grapes as well as those left untreated. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] Example 1

[0037] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0038] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heating magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0039] Example 2

[0040] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form 1, 2, and 3% (w / v) light yellow chitosan acetic acid solutions. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", or "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0041] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heating magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0042] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0043]

[0044] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, and n is the number of carbon atoms introduced after chitosan modification.

[0045]

[0046] From the mechanical properties of the samples, the layered porous block chitosan formed by freeze-drying 1% chitosan has poor hardness, the layered porous block chitosan formed by freeze-drying 2% chitosan has just the right hardness and elasticity, and the layered porous block chitosan formed by freeze-drying 3% chitosan has good hardness but slightly poor elasticity. Combined with the degree of substitution, 2% chitosan concentration is the best.

[0047] Example 3

[0048] Preparation of block porous chitosan: Dissolve chitosan powder in 0.5, 1, 1.5, 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0049] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heating magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0050] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0051]

[0052] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0053] The number of carbon atoms introduced into chitosan after modification.

[0054]

[0055] As the concentration of acetic acid increases, the pore size of the formed Cu-B-CS gradually increases, so the degree of substitution increases, but high concentrations will change the internal structure of the layered porous chitosan, resulting in a decrease in the degree of substitution.

[0056] Example 4

[0057] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in dry ice / ethanol. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form layered porous block chitosan. The freeze-dried sample is neutralized in 1, 2.5, 5, 7.5, 10% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinse off the excess acid and alkali with deionized water, and then wash with alcohol and dry at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0058] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heating magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0059] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0060]

[0061] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0062] The number of carbon atoms introduced into chitosan after modification.

[0063]

[0064] The degree of substitution shows a trend of first increasing and then decreasing with the increase of sodium hydroxide concentration. Under the same neutralization time, different sodium hydroxide concentrations cause changes in the degree of neutralization, which in turn causes changes in the pore structure, so the degree of substitution will also change.

[0065] Example 5

[0066] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in dry ice / ethanol. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form layered porous block chitosan. Neutralize the freeze-dried sample in 5% (w / v) sodium hydroxide ethanol aqueous solution for 5, 15, and 30 minutes, then rinse off excess acid and alkali with deionized water, and then wash with alcohol and dry at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0067] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heating magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0068] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0069]

[0070] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0071] The number of carbon atoms introduced into chitosan after modification.

[0072]

[0073] With the extension of neutralization time, the degree of substitution increases first and then decreases. The length and completeness of neutralization time will affect the pore structure of block porous chitosan, thus causing changes in the degree of substitution.

[0074] Example 6

[0075] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0076] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the molar ratio of amino group to aldehyde group of 1:1, 1:2, 1:4, 1:6, 1:8, dissolve cinnamaldehyde in ethanol aqueous solution, then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heated magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0077] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0078]

[0079] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0080] The number of carbon atoms introduced into chitosan after modification.

[0081]

[0082] As the molar ratio of amino groups to aldehyde groups increases, the degree of substitution gradually increases. When the molar ratio reaches 1:4, the grafting reaction reaches saturation and the degree of substitution almost stops increasing. Therefore, considering the economy and output, a molar ratio of 1:4 is the best option.

[0083] Example 7

[0084] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0085] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a constant temperature heating magnetic stirrer at 20, 40, 60, and 80 ° C, and react for 12 hours. After the reaction is completed, ethanol is replaced every 12 hours, and this operation is repeated until the unreacted cinnamaldehyde is removed. Finally, vacuum drying to constant weight is obtained to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0086] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0087]

[0088] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0089] The number of carbon atoms introduced into chitosan after modification.

[0090]

[0091] The degree of substitution is greatly affected by the reaction temperature of the grafting reaction. The degree of substitution increases first and then decreases with the increase of reaction temperature. When the reaction temperature reaches 60℃, the degree of substitution is the highest.

[0092] Example 8

[0093] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS).

[0094] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, then pour it into a flat-bottomed flask, and place it in a 60℃ constant temperature heated magnetic stirrer to react for 2, 4, 8, 12, and 24 hours respectively. After the reaction is completed, ethanol is replaced every 12 hours, and this operation is repeated until the unreacted cinnamaldehyde is removed. Finally, vacuum drying is performed to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0095] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0096]

[0097] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0098] The number of carbon atoms introduced into chitosan after modification.

[0099]

[0100] The degree of substitution is related to the reaction time of the grafting reaction. The grafting reaction changes rapidly with time within the first 4 hours of the reaction, and the reaction rate is high. As the reaction proceeds, the degree of substitution tends to stabilize and reaches the maximum value at 12 hours. When the reaction time exceeds 12 hours, the degree of substitution begins to decrease.

[0101] Example 9

[0102] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends or one end of the copper plate in liquid nitrogen. These two freezing methods are called bidirectional freezing and unidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"; "copper single", i.e. "Cu-U"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. The freeze-dried sample is neutralized in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinsed with deionized water to remove excess acid and alkali, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan (Cu-B-CS, Cu-U-CS).

[0103] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of block porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, then pour it into a flat-bottomed flask, and place it in a 60℃ constant temperature heated magnetic stirrer to react for 12 hours. After the reaction is completed, ethanol is replaced every 12 hours, and this operation is repeated until the unreacted cinnamaldehyde is removed. Finally, vacuum drying is performed to constant weight to obtain block Schiff base preservative materials (Cu-B-CS-Cin, Al-B-CS-Cin, Fe-B-CS-Cin).

[0104] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0105]

[0106] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, and n is the number of carbon atoms introduced after chitosan modification.

[0107]

[0108] Compared with bidirectional freezing, unidirectional freezing only forms a longitudinal temperature gradient, while bidirectional freezing forms two temperature gradients, namely, transverse and longitudinal temperature gradients. Therefore, the freezing rate of unidirectional freezing is relatively smaller, thus forming a smaller pore structure. Therefore, the degree of substitution is lower than that of the sample formed by bidirectional freezing.

[0109] Example 10

[0110] Example 1 The chitosan porous material after freeze-drying and neutralization was observed by scanning electron microscope. The sample was sprayed with gold before observation, and the cross-sectional diagrams of the sample in the xy, yz and xz directions were observed at different magnifications.

[0111] Depend on Figure 1 It can be seen that the structure of the porous chitosan obtained after freeze drying is a highly aligned layered porous structure. After neutralization with sodium hydroxide, the structure also changes greatly, and the final sample structure becomes a honeycomb structure.

[0112] Embodiment 11

[0113] Fourier transform infrared spectra of the block porous chitosan, the grafted Schiff base material and cinnamaldehyde in Example 1. The samples were subjected to full infrared reflection measurement with a scanning range of 4000 cm -1 ~500cm -1 , the scanning frequency is 32 times.

[0114] Depend on Figure 2 It can be seen that compared with the ungrafted porous chitosan, the -1 A new peak appears at 745 cm -1 and 686cm -1 The CH peak of the benzene ring on cinnamaldehyde and the stretching vibration peak of olefins appeared at the bottom, proving that the grafting of chitosan and cinnamaldehyde was successful.

[0115] Example 12

[0116] pH response release experiment of the grafted Schiff base material in Example 1. Take a whole piece (0.06 g is taken in the actual process, but there is often a slight error due to the difference between the measurement and the actual finished product) sample in a centrifuge tube, dissolve it in 50 mL of buffer solution with different pH values, take 5 mL of samples every 2 h, 5 h, 8 h, 10 h, 24 h, 48 h, 72 h, and 96 h, and add the corresponding buffer solution to the total volume to 50 mL after sampling to study its release behavior, and set up three times in parallel.

[0117]

[0118] Depend on Figure 3 It can be seen that the cumulative release rate is different under different pH values. As the pH value decreases, the cumulative release rate gradually increases. Under acidic conditions, the cumulative release rate reaches a maximum of 94.95%, while under moderately alkaline conditions, the cumulative release rate is less than 10%, indicating that it can respond to release under acidic conditions and remain stable under moderately alkaline conditions. Moreover, under pH = 5, 7, and 9, the cumulative release rate gradually increases, indicating that the Schiff base sample can achieve a sustained release effect, while under pH = 3, it shows a trend of first increasing and then decreasing, reaching the maximum value of the cumulative release rate after 48 hours, which may be related to the fact that the sample can be completely dissolved at 48 hours. After complete dissolution, the cumulative release rate gradually decreases.

[0119] Example 13

[0120] Simulation experiment of fruits and vegetables under high humidity and acidity of the grafted Schiff base material in Example 1. Take 1g of sample in a fresh-keeping box, and use the principle that calcium carbonate and hydrochloric acid react to generate carbon dioxide to form a device with different carbon dioxide contents, and use the salt solution generated by the reaction to meet the high humidity requirements, thereby simulating the headspace microenvironment of fruits and vegetables under high humidity and acidity. Take samples every 1d, dissolve them in pH buffer after sampling, measure the absorbance at 292nm by ultraviolet spectrophotometer, and compare with the initial content, the difference is the release amount.

[0121] Depend on Figure 4It can be seen that in the simulated high humidity and acidic environment of fruits and vegetables, under different concentrations of carbon dioxide, there is a trend of continuous release, which is consistent with the release trend under acidic buffer solution, and the release amount gradually increases with the increase of carbon dioxide concentration.

[0122] Embodiment 14

[0123] The Cu-B-CS-Cin in Example 1 was applied to bananas. 0.6 g of sample and 300 g of bananas were placed in a medium-sized fresh-keeping bag (18×22 cm) at the same time. The sample addition amount was 2 g / kg of bananas. No sample and cinnamaldehyde were used as blank and control, respectively. The hardness and total bacterial count of the bananas were measured at 0, 3, 5, and 7 days.

[0124] Depend on Figure 5 and Figure 6 It can be seen that in the first three days, cinnamaldehyde has the best preservation effect, which can reduce the decline in hardness and inhibit the growth of microorganisms. However, due to the excessive local concentration in the early stage, it caused diseases in the later stage, that is, the degree of corruption was more serious than that of the blank. However, as the storage time increases, due to the continuous release of Cu-B-CS-Cin, compared with the blank and cinnamaldehyde groups, it can effectively delay the decline in hardness and the growth of the total number of colonies.

[0125] Embodiment 15

[0126] A powdered Schiff base derivative (Powder-CS-Cin) was prepared according to the method in the patent "Preparation method and application of a pH-responsive intelligent controlled-release antibacterial preservative for packaging", and 0.6 g of the powdered Schiff base derivative prepared above and 0.6 g of the block Cu-B-CS-Cin prepared in Example 1 were respectively applied to a fresh-keeping bag containing 300 g of bananas, and the sample addition amount was 2 g / kg bananas. A blank was used as a control, and the hardness and total colony count of the bananas were measured at 0, 3, 5, and 7 days.

[0127] In the 7-day storage experiment, the blank group showed obvious browning on the 7th day, while the block Schiff base group showed partial browning in the Powder-CS-Cin group and slight browning in the Cu-B-CS-Cin group. Figure 7 In the experiment, compared with the blank, the CS-Cin group can delay the decrease of hardness, and the block porous group is higher than the powder group. The hardness of the Powder-CS-Cin group can maintain a good state in the first 5 days. When extended to the 7th day, the Powder-CS-Cin group is significantly lower than the Cu-B-CS-Cin group, indicating that the block porous Cu-B-CS-Cin has a better sustained release effect. Figure 8It can be seen that the total colony counts of the Cu-B-CS-Cin group and the Powder-CS-Cin group were significantly lower than that of the blank group, but the colony count of the Cu-B-CS-Cin group was lower than that of the Powder-CS-Cin group, and the increase in the total colony count of the Powder-CS-Cin group was higher than that of the Cu-B-CS-Cin group from 5 to 7 days, which to a certain extent proves that the blocky porous Cu-B-CS-Cin has a better preservation effect.

[0128] Example 16

[0129] The Cu-B-CS-Cin in Example 1 was applied to grapes. 0.1g of sample and 100g of grapes were placed in a small fresh-keeping bag (15.4×17.5cm) at the same time. The sample addition amount was 1g / kg of grapes. No sample and cinnamaldehyde were used as blank and control, and the hardness and total colony count of the grapes were measured at 0, 3, and 5 days. During the storage process, a small amount of corruption appeared in the blank and Cu-B-CS-Cin groups on the 3rd day, that is, a small amount of colonies appeared, and no colonies appeared in the cinnamaldehyde group. On the 4th day, the corruption rates of the Cu-B-CS-Cin group and the blank group increased, and there was no difference between the two. The cinnamaldehyde group did not show obvious corruption, indicating that cinnamaldehyde can inhibit the growth of colonies. However, due to the low respiration intensity of grapes and the low acidic stimulation in the environment, Cu-B-CS-Cin can hardly release cinnamaldehyde, resulting in no fresh-keeping effect. On the other hand, judging from the measured indicators, Fig. 9 , 10 In the first five days of storage, it can be seen that there is no difference in the hardness value and total bacterial count between the Cu-B-CS-Cin group and the blank group. Cinnamaldehyde can significantly delay the decrease in hardness value and inhibit the growth of microorganisms. Therefore, for grapes with low respiration intensity, the Cu-B-CS-Cin group does not show freshness preservation performance.

[0130] Comparative Example 1

[0131] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan.

[0132] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of layered porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heated magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain a block Schiff base preservative material (Cu-B-CS-Cin).

[0133] Degree of substitution: The C and N contents of the sample are measured by an element analyzer, and the degree of substitution (DS) of the sample is calculated according to the formula:

[0134]

[0135] Where (C / N) m is the C / N ratio of Schiff base derivatives, (C / N) O is the C / N of porous chitosan, n is

[0136] The number of carbon atoms introduced into chitosan after modification.

[0137]

[0138] The layered porous chitosan obtained after freeze-drying is directly used for grafting reaction without neutralization, and the degree of substitution of the obtained Schiff base derivative is very low. The main reason is that the layered porous chitosan after freeze-drying contains acetic acid and presents an acidic environment. The imine bond formed by the grafting of chitosan and cinnamaldehyde is greatly affected by pH and will undergo hydrolysis in an acidic environment, affecting the grafting reaction. Therefore, the degree of substitution is very low.

[0139] Comparative Example 2

[0140] Preparation of block porous chitosan: Dissolve chitosan powder in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution. Place the chitosan solution in a silicone mold above a copper plate, and immerse both ends of the copper plate in liquid nitrogen. This freezing method is called bidirectional freezing (abbreviated as "copper double", i.e. "Cu-B"). After the solution is completely frozen, take it out of the silicone mold and dry it in a freeze dryer to form a layered porous block chitosan. Neutralize the freeze-dried sample in a 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, then rinse off the excess acid and alkali with deionized water, and then wash with alcohol, and use filter paper to absorb the liquid on the surface to obtain block porous chitosan (Cu-B-CS).

[0141] Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: Weigh a certain mass of the above porous chitosan and place it in a flat-bottomed flask, calculate the required mass of cinnamaldehyde (Cin) according to the 1:4 molar ratio of amino group to aldehyde group, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottomed flask, put the flask into a 60℃ constant temperature heating magnetic stirrer, and react for 12h. After the reaction is completed, change ethanol every 12h, and repeat this operation until the unreacted cinnamaldehyde is removed. Finally, vacuum dry to constant weight to obtain Schiff base preservative material (Cu-B-CS-Cin).

[0142] Directly grafting cinnamaldehyde to the blocky porous chitosan without drying after neutralization, water washing and alcohol washing of the layered porous chitosan cannot form a blocky Schiff base fresh-keeping material. Since the structure of the porous chitosan becomes loose during the neutralization and water washing process, the structure is destroyed during the grafting process, and thus a blocky Schiff base fresh-keeping material cannot be formed in the end. Therefore, drying after neutralization, water washing and alcohol washing is necessary for preparing a blocky porous Schiff base fresh-keeping material.

[0143] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A block-shaped porous intelligent controlled-release fresh-keeping material, characterized in that: The fresh-keeping material is a grafted cinnamaldehyde with a porous structure, and the grafted cinnamaldehyde comprises block-shaped porous chitosan and cinnamaldehyde; The preparation method of the block-shaped porous intelligent controlled-release fresh-keeping material is as follows: Preparation of block porous chitosan by bidirectional freezing method: chitosan powder is dissolved in 2% (v / v) acetic acid solution to form a 2% (w / v) light yellow chitosan acetic acid solution; the chitosan solution is bidirectionally frozen and then taken out from the silica gel mold, and dried using a freeze dryer to form layered porous block chitosan; the freeze-dried sample is neutralized in 5% (w / v) sodium hydroxide ethanol aqueous solution for 15 minutes, and then the excess acid and alkali are rinsed with deionized water, and then washed with alcohol and dried at room temperature to constant weight to obtain block porous chitosan; Preparation of block porous chitosan-cinnamaldehyde Schiff base preservative material: weigh a certain mass of block porous chitosan and place it in a flat-bottom flask, calculate the required mass of cinnamaldehyde (Cin) according to the molar ratio of amino group to aldehyde group of 1:4, dissolve cinnamaldehyde in ethanol aqueous solution, and then pour it into the flat-bottom flask, put the flask into a 60°C constant temperature heating magnetic stirrer, and react for 12 hours; after the reaction is completed, replace ethanol every 12 hours, and repeat this operation until the unreacted cinnamaldehyde is removed; Finally, vacuum drying is performed to constant weight to obtain a block-shaped Schiff base preservative material.

2. The block-shaped porous intelligent controlled-release fresh-keeping material according to claim 1, characterized in that: The fresh-keeping material is a fresh-keeping agent for fruits and vegetables.

Citation Information

Patent Citations

  • Preparation method and application of pH-responsive intelligent controlled-release antibacterial preservative for packaging

    CN112715646A